Modulation of Interleukin-17 By Tumor Necrosis Factor Alpha During the Immune Response to Borrelia Burgdorferi - (:unkn) unknown (My University, 2013)
Arthritis is one of the main complications of late-stage Lyme borreliosis. Cytokines play an important role in the persistent inflammation that is elicited by the causative agent of disease, Borrelia burgdorferi. Tumor necrosis factor alpha (TNF-alpha) is a pro-inflammatory cytokine that is induced by B. burgdorferi and that has been implicated in development of arthritis. However, in a mouse model of Lyme arthritis, treatment with anti-TNF-alpha; antibodies increased the severity of disease. By contrast, injection of recombinant TNF-alpha; ameliorated arthritis in this model. These findings suggested that other factors might be involved during the development of Lyme arthritis. One possible factor may be interleukin-17 (IL-17), a pro-inflammatory cytokine mainly produced by T helper 17 cells. IL-17 has been implicated in the development of Lyme arthritis. Treatment with anti-IL-17 antibodies reduces the inflammatory outcome in animal models of disease. However, it is not known how TNF-alpha; affects the response of IL-17 to B. burgdorferi. The hypothesis of this thesis is that TNF-alpha; will regulate the immune response to B. burgdorferi infection by decreasing IL-17 production. Modulation of IL-17 during the immune response to B. burgdorferi was analyzed in wild-type and interleukin-10 (IL-10)-deficient mice treated with anti-TNF-alpha; antibodies. We found that anti-TNF-alpha; antibody treatment increased paw inflammation in both wild-type and IL-10 deficient mice. In addition, cell cultures from B. burgdorferi-infected, wild-type mice treated with anti-TNF-alpha; antibodies typically produced a greater amount of IL-17 than untreated controls, suggesting that TNF-alpha; decreases IL-17 levels following infection. Additional treatment of anti-TNF-alpha; antibody-treated mice with anti-IL-17 antibodies lessened the severity of paw swelling. Our results indicate that TNF-alpha; can play a protective role during the immune response to B. burgdorferi infection by restraining the production of IL-17.
Keywords: Interleukin-17; Lyme Arthritis; Tumor Necrosis Factor-Alpha